Digital Skills dan Pelatihan Berbasis Kompetensi dalam Peningkatan Kinerja UMKM: A Systematic Literature Review - Natalia Marijani Wijanto; Syamsul Hadi Senen; Rofi Rofaida (SAFE-Network, 2026)
In the era of digital transformation, MSMEs are required to enhance business performance through the effective use of digital technologies. However, limited digital skills and inadequate human resource training remain major challenges for MSMEs. This study aims to address main research question concerning the role of digital skills and competency-based training in improving MSME performance based on empirical evidence. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Relevant articles were identified through a systematic search of the Scopus database covering the publication period from 2016 to 2026 and were subsequently screened using predefined inclusion and exclusion criteria. The quality of the selected studies was assessed using the JBI Critical Appraisal Tools according to each study’s research design. Out of 226 identified articles, 11 studies met the selection and quality assessment criteria and were further analyzed using a narrative synthesis approach. The synthesis reveals that digital skills and competency-based training function as strategic human capital mechanisms that enhance MSME performance, particularly when training interventions are contextualized, practice-oriented, and supported by organizational readiness. Nevertheless, the existing evidence is largely dominated by cross-sectional study designs, which limits causal inference and the understanding of long-term impacts. This review concludes that digital competency development is a strategic factor for MSMEs and highlights the need for sustainable training approaches and integrated policy support.